CORRECTION TO: LOW-COST BIOMECHANICAL SYSTEM FOR THE EVALUATION OF PARKINSON'S (SN COMPUTER SCIENCE, (2024), 5, 1, (168), 10.1007/S42979-023-02445-1) - AUCCAHUASI, WILVER (2024)
CORRECTION TO: SN COMPUTER SCIENCE (2024) 5:168, HTTPS://DOI.ORG/10.1007/S42979-023-02445-1 IN THIS ARTICLE, THE AFFILIATION OF THE AUTHORS (ABILIO CUZCANO, SANTIAGO RUBIÑOS, CÉSAR SANTOS, JESSICA MEZA, MOISÉS TONGO AND JOSÉ LUIS HERRERA SALAZAR) WERE INCORRECT AS: WILVER AUCCAHUASI1, JACOB ASTOCONDOR2, LUCAS HERRERA3, KARIN ROJAS4, ABILIO CUZCANO1, EDITH NEGLIA5, JUAN GRADOS6, SANTIAGO RUBIÑOS1, CÉSAR SANTOS1, JESSICA MEZA1, MOISÉS TONGO7, WILSON MARIN8, JOSÉ LUIS HERRERA SALAZAR91UNIVERSIDAD PRIVADA DEL NORTE, LIMA, PERÚ 2UNIVERSIDAD NACIONAL DEL CALLAO, LIMA, PERÚ 3UNIVERSIDAD CONTINENTAL, HUANCAYO, PERÚ 4UNIVERSIDAD TECNOLÓGICA DEL PERÚ, LIMA, PERÚ 5UNIVERSIDAD CIENTÍFICA DEL SUR, LIMA, PERÚ 6UNIVERSIDAD NACIONAL FEDERICO VILLARREAL, LIMA, PERÚ 7UNIVERSIDAD SAN IGNACIO DE LOYOLA, LIMA, PERÚ 8UNIVERSIDAD CÉSAR VALLEJO, LIMA, PERÚ 9UNIVERSIDAD NACIONAL TECNOLOGICA DE LIMA SUR, LIMA, PERÚ BUT, THEY SHOULD BE AS GIVEN BELOW: WILVER AUCCAHUASI1, JACOB ASTOCONDOR2, LUCAS HERRERA3, KARIN ROJAS4, ABILIO CUZCANO2, EDITH NEGLIA5, JUAN GRADOS6, SANTIAGO RUBIÑOS2, CÉSAR SANTOS2, JESSICA MEZA2, MOISÉS TONGO7, WILSON MARIN8, JOSÉ LUIS HERRERA SALAZAR91UNIVERSIDAD PRIVADA DEL NORTE, LIMA, PERÚ 2UNIVERSIDAD NACIONAL DEL CALLAO, LIMA, PERÚ 3UNIVERSIDAD CONTINENTAL, HUANCAYO, PERÚ 4UNIVERSIDAD TECNOLÓGICA DEL PERÚ, LIMA, PERÚ 5UNIVERSIDAD CIENTÍFICA DEL SUR, LIMA, PERÚ 6UNIVERSIDAD NACIONAL FEDERICO VILLARREAL, LIMA, PERÚ 7UNIVERSIDAD NACIONAL DANIEL ALCIDES CARRIÓN, PASCO, PERÚ 8UNIVERSIDAD CÉSAR VALLEJO, LIMA, PERÚ 9UNIVERSIDAD NORBERT WIENER, LIMA, PERÚ THE ORIGINAL ARTICLE HAS BEEN CORRECTED. © THE AUTHOR(S), UNDER EXCLUSIVE LICENCE TO SPRINGER NATURE SINGAPORE PTE LTD 2024.